Biogas reformation over pr-promoted ni/mgo - Shaik Ismail, Mohamed Ali (2014)
Promoting rare earth element into commercial catalyst has become interesting research in designing the best catalyst for methane dry reforming. 1wt%, 3wt% and 5wt% Pr loadings into Ni/MgO were prepared by wet-impregnation method and calcined at 973 K. The prepared catalyst was characterized using N2physisorption, field emission scanning electron microscopy (FESEM), X-ray diffraction spectroscopy (XRD) andenergy dispersive X-ray spectroscopy (EDX). The BET surface area increasedwhen the Pr loading percentage was increased. The surface area for 1wt% Pr loading of Pr-Ni/MgO was 14.3 m2/g and 28.11 m2/g for 5wt% Pr loading. The structure of the 5wt% Pr promoted Pr-Ni/MgO was much closely packed compared to the non-promoted Ni/MgO that captured by FESEM. Furthermore, XRD peak shows no peak of PrO for 5% Pr-Ni/MgO as the interaction was strong and well dispersed that didn’t allow the XRD to detect. This statement was further supported by EDX result that showed the Pr was well dispersed on the catalyst. The MgO peak was found at 28.34o, 37.02o, 42.99o, 62.99o, 62.40o, 74.85o and 78.83o. Reaction studies over the Pr-Ni/MgO showed that the 5wt% promoted consistently yielded the best reaction at 1073, 1123 and 1173 K respectively. The conversion can reach ca. 61.44 % at 1173K when reactant volumetric flow ratio, CO2/CH4 was fixed at unity. In addition, the product H2/CO ratioswere found to be less than 3.0 which were similar to the values reported in most of the other studies. The reaction power order for the CH4 and CO2 was 0.6111 and 0.4274 respectively whilstthe activation energy and activity for the reaction over 5wt% Pr-Ni/MgO catalyst was 66.10kJ/mol and 0.372.